2013
DOI: 10.1002/acr.22015
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Deviations During Level Walking Associated With Knee Osteoarthritis: A Systematic Review and Meta‐Analysis

Abstract: Objective. To identify which gait deviations are consistently associated with knee osteoarthritis (KOA) and how these are influenced by disease severity, the involved compartment, and sex. Methods. Five electronic databases and reference lists of publications were searched. Cross-sectional, observational studies comparing temporospatial variables, joint kinematics, and joint moments between individuals with KOA and healthy controls or between KOA subgroups were considered for review. Only publications scoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 189 publications
(133 citation statements)
references
References 61 publications
5
121
1
6
Order By: Relevance
“…This extends to recent systematic reviews of KAM calculation in gait studies in people with knee OA 20. The KAM may influence OA progression in a variety of ways; disease progression has been linked to (i) the overall peak magnitude (usually the early stance peak),1 (ii) the KAM impulse2 and (iii) external foot rotation—which is only affected by the late stance peak KAM 21.…”
Section: Discussionmentioning
confidence: 56%
“…This extends to recent systematic reviews of KAM calculation in gait studies in people with knee OA 20. The KAM may influence OA progression in a variety of ways; disease progression has been linked to (i) the overall peak magnitude (usually the early stance peak),1 (ii) the KAM impulse2 and (iii) external foot rotation—which is only affected by the late stance peak KAM 21.…”
Section: Discussionmentioning
confidence: 56%
“…Ten additional articles were included from one author's personal collection (CN). As these studies reported on 143 different biomechanical variables, further analysis was conducted only on variables that were reported by three or more papers 32. This reduced the number of biomechanical variables to 14, from 27 articles.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with strength deficits in other lower extremity muscle groups (i.e., quadriceps), cross-sectional data have shown that compared to non-arthritic age-matched individuals, people with knee OA have significantly reduced isometric (~24%) and isokinetic (6-42%) hip abductor strength (Costa et al, 2010;Hinman et al, 2010). During walking, people with knee OA show alterations in parameters of the external knee adduction moment (KAM) compared to people without OA (Baliunas et al, 2002;Mundermann et al, 2004;Landry et al, 2007;Astephen et al, 2008;Mills et al, 2013). The external knee adduction moment, measured via three-dimensional gait analysis, is indicative of the medial-to-lateral joint load distribution and is often used as a surrogate for medial knee compartment loading (Zhao et al, 2007;Meyer et al, 2013).…”
Section: Introductionmentioning
confidence: 89%